Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1089/end.2006.0140
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Vesical Diverticulectomy

Abstract: Laparoscopic diverticulectomy is technically feasible and safe and may represent an alternative to the standard open procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 15 publications
2
13
0
Order By: Relevance
“…Consequently, it remains essential that obstruction is relieved either before, concomitantly or after the management of the diverticulum. Concerns were raised for the concurrent management of these 2 entities, largely based on the potential necessity of bladder irrigation and possible bladder distention after TUR-P, which might jeopardize bladder integrity following closure [8]. Due to hemostatic properties of potassium-titanyl-phosphate (KTP) laser, bleeding is minimal after PVP and bladder irrigation is generally avoidable.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it remains essential that obstruction is relieved either before, concomitantly or after the management of the diverticulum. Concerns were raised for the concurrent management of these 2 entities, largely based on the potential necessity of bladder irrigation and possible bladder distention after TUR-P, which might jeopardize bladder integrity following closure [8]. Due to hemostatic properties of potassium-titanyl-phosphate (KTP) laser, bleeding is minimal after PVP and bladder irrigation is generally avoidable.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the need for continuous irrigation after TURP and during the diverticulectomy may represent a difficulty, because the bladder can be inflated and deflated intraoperatively to facilitate dissection. 6,17,18 The performance of PVP minimizes the need for irrigation intraoperatively (diverticulectomy) and postoperatively, rendering the sequential management of benign prostatic hyperplasia and bladder diverticulum feasible and safe. 20 LESS has been introduced as a further development of minimally invasive surgery and laparoscopy.…”
mentioning
confidence: 99%
“…Complications were not observed while blood loss was similar to that of the laparoscopic literature. [1][2][3][4][5][6]17,18,20,21 Conclusion LESS bladder diverticulectomy proved to be feasible with comparable postoperative outcome to that of the laparoscopic procedure. The use of prebent instruments improved intraoperative ergonomics.…”
mentioning
confidence: 99%
“…As a result, different methods such as intraoperative cystoscopy have been introduced to overcome identification challenges. As a useful technique, Abdel-Hakim et al [14] reported that masses could be located by inflating and deflating the bladder with air during robot-assisted LPC. The use of intraoperative real-time transrectal ultrasound guidance was also reported to be helpful in patients whose tumors were lodged within a para-ureteral diverticulum [4].…”
Section: Discussionmentioning
confidence: 99%